Ag-Pt high-performance low-cost three-way catalyst and preparation method thereof
By coating the cerium-zirconium solid solution with Pt colloid and loading it on Ag-modified molecular sieve, the problem of sintering and aggregation of precious metal particles at high temperatures is solved, and the high performance and low cost of the catalyst are achieved.
Patent Information
- Application Number
- CN202411644593.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-21
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to an Ag-Pt high-performance and low-cost three-way catalyst and a preparation method thereof. Background Art
[0002] In 2019, the global automobile exhaust treatment catalyst industry's demand for platinum, palladium, and rhodium accounted for 34.0%, 84.2%, and 88.2% of the total annual demand for platinum group metals, respectively. Among them, China's automobile exhaust treatment catalyst industry's demand for platinum, palladium, and rhodium were 4.7 tons, 83.0 tons, and 9.9 tons, respectively, accounting for 5.3%, 27.7%, and 31.5% of the global industry's total demand, respectively. China has begun to fully implement the National VI emission standards in 2020. With the gradual improvement of automobile exhaust treatment standards, the demand for platinum, palladium, and rhodium will continue to increase. In recent years, the ability to simultaneously reduce CO, HC, and NO in automobile exhaust has been x The demand for automotive three-way catalysts with significantly reduced content of three harmful gases is increasing, which has also led to a significant increase in the demand for palladium and rhodium, resulting in increasingly prominent contradictions between resource supply and demand and continued high prices of precious metals. The Chinese automobile industry is particularly urgent in its demand for cost control of three-way catalysts.
[0003] It is known that the dosage and dispersion of the above-mentioned noble metals play a decisive role in the activity of the catalyst. However, in the preparation process of the three-way catalyst, the noble metal particles dispersed on the surface of the carrier often become larger due to high temperature, and the dispersion decreases, thereby reducing the activity of the catalyst.
[0004] Based on the above situation, it is an urgent technical problem to develop a three-way catalyst as soon as possible that can efficiently disperse precious metals, is not easy to sinter and agglomerate at high temperatures, or uses cheap precious metals as substitutes and has stronger catalytic performance. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the inventors have found through research that the cerium zirconium solid solution can be coated with Pt colloid and then loaded on a Ag-modified molecular sieve, and then sprayed on a cordierite matrix to prepare a high-performance, low-cost three-way catalyst. The cerium zirconium solid solution is used to coat the Pt colloid to effectively avoid the sintering and agglomeration of the noble metal Pt at high temperatures. On the other hand, the high specific surface area of the molecular sieve promotes the high dispersion of Ag, exposes more active centers, and can reduce the amount of noble metals and improve catalytic performance. Compared with the traditional Pt and Rh schemes, the use of Ag, Pt and the traditional Pt, Rh schemes have a lower price. While reducing production costs, the coating applied to the cordierite carrier after optimization shows higher catalytic performance.
[0006] Specifically, the technical solution adopted by the present invention is as follows:
[0007] On the one hand, the present invention provides a Ag-Pt high-performance and low-cost three-way catalyst, which is prepared by coating a cerium-zirconium solid solution with a Pt colloid, loading the cerium-zirconium solid solution with a Ag-modified molecular sieve, and then spraying the cerium-zirconium solid solution on a carrier.
[0008] Furthermore, the present invention provides the Ag-Pt high-performance and low-cost three-way catalyst, wherein the molecular sieve is selected from one or more of MFI-type ZSM-5, CHA-type SSZ-13, Beta-type, and HY-type molecular sieves.
[0009] Furthermore, the present invention provides the Ag-Pt high-performance and low-cost three-way catalyst, wherein the weight ratio of the molecular sieve to silver nitrate is 20 to 180:1.
[0010] Furthermore, the present invention provides the Ag-Pt high-performance and low-cost three-way catalyst, wherein the mass ratio of Ag to Pt is 10:1 to 1:10.
[0011] Furthermore, the present invention provides the Ag-Pt high-performance and low-cost three-way catalyst, wherein the molecular sieve accounts for 10 to 40% by weight in the entire coating.
[0012] Furthermore, the present invention provides the Ag-Pt high-performance and low-cost three-way catalyst, wherein the mass ratio of CeO2 in the cerium-zirconium solid solution to the cerium-zirconium solid solution is 5% to 60%.
[0013] Furthermore, the present invention provides the Ag-Pt high-performance and low-cost three-way catalyst, wherein the mass ratio of yttrium oxide, lanthanum oxide and praseodymium oxide in the cerium-zirconium solid solution is 1% to 10%.
[0014] Furthermore, the present invention provides the Ag-Pt high-performance and low-cost three-way catalyst, wherein the carrier is a ceramic carrier or a cordierite carrier.
[0015] On the other hand, the present invention provides a method for preparing a Ag-Pt high-performance and low-cost three-way catalyst, comprising the following steps:
[0016] Step (1) dispersing the molecular sieve in water, dropping a silver nitrate solution, stirring evenly, dropping an ammonium carbonate solution, controlling the pH value to be 4-6, filtering out the molecular sieve, vacuum drying at 40-60° C. for 8-12 h, and calcining at 300-500° C. for 1-3 h to obtain an Ag-modified molecular sieve;
[0017] Step (2) dissolving hydrazine hydrate, polydextrose and ethanol in water, dropping platinum nitrate into it, bathing it in water at 50-80° C. for 4-8 hours, then washing it with ethanol several times and then dispersing it in ethanol to obtain Pt colloid;
[0018] Step (3) dissolving one or more selected from yttrium nitrate, lanthanum nitrate, praseodymium nitrate, cerium nitrate and zirconium nitrate in water, adding the Pt colloid obtained in step (2), and then heating in a water bath at 50-90°C for 2-4 hours, then adding the Ag-modified molecular sieve obtained in step (1) and continuing stirring, and adding ammonia water to adjust the pH value to 4-6 to form a sol; spraying the sol on the surface of the cordierite carrier by rotary spraying technology, repeatedly spraying for several times, aging, drying at 40-80°C for 8-12 hours, and calcining at 400-600°C for 2-4 hours to obtain a supported cordierite catalyst.
[0019] Preferably, in the method for preparing the Ag-Pt high-performance and low-cost three-way catalyst of the present invention, the ratio of hydrazine hydrate, polydextrose, ethanol and platinum nitrate is 4-10 mL: 2-5 g: 20-60 mL: 0.1-1 g.
[0020] Preferably, in the method for preparing the Ag-Pt high-performance and low-cost three-way catalyst of the present invention, the coating amount of the sol prepared in step (3) sprayed on the surface of the cordierite carrier reaches 200 g / L.
[0021] The advantages and beneficial effects of the present invention are:
[0022] 1) The use of cerium-zirconium solid solution to coat Pt colloid effectively avoids the sintering and agglomeration of precious metal Pt at high temperatures, and the high specific surface area of the molecular sieve promotes the high dispersion of Ag, exposing more active centers, and fully improving the catalyst to activate CO, HC and NO in automobile exhaust. x The catalytic performance of harmful gases such as carbon dioxide has achieved excellent results in removing the above gases.
[0023] 2) Compared with the traditional Pt and Rh schemes, the use of Ag-modified molecular sieves not only reduces the amount of precious metals used, but also uses cheaper Ag as a substitute. While reducing production costs, the optimized coating applied to the cordierite carrier shows unexpectedly higher catalyst performance. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention is specifically described below in conjunction with the embodiments. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention. The raw materials, reagents, equipment, etc. used in the following embodiments are all commercially available or conventionally available.
[0025] Example 1
[0026] A Ag-Pt high-performance and low-cost three-way catalyst, the preparation method of which comprises the following steps:
[0027] Step (1) 200 g of MFI type ZSM-5 molecular sieve is dispersed in water, and a silver nitrate solution (containing 2 g of silver nitrate) is added dropwise, and after being stirred evenly, an ammonium carbonate solution is added dropwise, and the pH value is controlled to be 5. The molecular sieve is filtered out, vacuum dried at 50° C. for 10 h, and calcined at 400° C. for 2 h to obtain an Ag-modified molecular sieve.
[0028] Step (2) 3 mL of hydrazine hydrate, 3 g of polydextrose, and 40 mL of ethanol were dissolved in 100 g of water, and a platinum nitrate solution (containing 0.208 g of platinum nitrate) was added dropwise, and the mixture was placed in a water bath at 60° C. for 6 h, and then washed with ethanol several times and dispersed in ethanol to obtain a Pt colloid.
[0029] Step (3): Dissolve yttrium nitrate (20 g in terms of yttrium oxide), lanthanum nitrate (20 g in terms of lanthanum oxide), cerium nitrate (160 g in terms of cerium oxide), and zirconium nitrate (600 g in terms of zirconium oxide) in water, add the Pt colloid obtained in step (2), and place in a water bath at 80°C for 3 h, then add the Ag-modified molecular sieve obtained in step (1), continue stirring, and drop ammonia water to adjust the pH value to 5 to form a sol. Spray the sol onto the surface of the cordierite carrier by a rotary spraying technique, spray repeatedly for several times, age until the coating amount reaches 200 g / L, dry at 60°C for 10 h, and calcine at 500°C for 4 h to obtain a supported cordierite catalyst.
[0030] Example 2
[0031] A Ag-Pt high-performance and low-cost three-way catalyst, the preparation method of which comprises the following steps:
[0032] Step (1) 300 g of CHA type SSZ-13 molecular sieve was dispersed in water, and a silver nitrate solution (containing 6 g of silver nitrate) was added dropwise, and after stirring evenly, an ammonium carbonate solution was added dropwise, and the pH value was controlled to be 5. The molecular sieve was filtered out, vacuum dried at 50° C. for 10 h, and calcined at 400° C. for 2 h to obtain an Ag-modified molecular sieve.
[0033] Step (2) 40 mL of hydrazine hydrate, 20 g of polydextrose and 150 mL of ethanol were dissolved in 200 g of water, and a platinum nitrate solution (containing 6.23 g of platinum nitrate) was added dropwise, and the mixture was placed in a water bath at 60° C. for 6 h, and then washed with ethanol several times and dispersed in ethanol to obtain a Pt colloid.
[0034] Step (3): dissolve praseodymium nitrate (21 g in terms of praseodymium oxide), lanthanum nitrate (21 g in terms of lanthanum oxide), cerium nitrate (280 g in terms of cerium oxide) and zirconium nitrate (378 g in terms of zirconium oxide) in water, add the Pt colloid obtained in step (2), and place in a water bath at 80°C for 3 h. Then, add the Ag-modified molecular sieve obtained in step (1) and continue stirring. Add ammonia water to adjust the pH value to 5 to form a sol. Spray the sol onto the surface of the cordierite carrier by rotary spraying technology, spray repeatedly for several times, age until the coating amount reaches 200 g / L, dry at 60°C for 10 h, and calcine at 500°C for 4 h to obtain a supported cordierite catalyst.
[0035] Example 3
[0036] A Ag-Pt high-performance and low-cost three-way catalyst, the preparation method of which comprises the following steps:
[0037] Step (1) 540 g of Beta molecular sieve was dispersed in water, and a silver nitrate solution (containing 0.67 g of silver nitrate) was added dropwise, and after stirring, an ammonium carbonate solution was added dropwise, and the pH value was controlled to be 5. The molecular sieve was filtered out, vacuum dried at 50° C. for 10 h, and calcined at 400° C. for 2 h to obtain an Ag-modified molecular sieve.
[0038] Step (2) 30 mL of hydrazine hydrate, 16 g of polydextrose, and 170 mL of ethanol were dissolved in 200 g of water, and a platinum nitrate solution (containing 6.92 g of platinum nitrate) was added dropwise, and the mixture was placed in a water bath at 60° C. for 6 h, and then washed with ethanol several times and dispersed in ethanol to obtain a Pt colloid.
[0039] Step (3): praseodymium nitrate (45 g in terms of praseodymium oxide), yttrium nitrate (45 g in terms of yttrium oxide), cerium nitrate (540 g in terms of cerium oxide) and zirconium nitrate (270 g in terms of zirconium oxide) are dissolved in water, and the Pt colloid obtained in step (2) is added, and the mixture is placed in a water bath at 80°C for 3 hours, and then the Ag-modified molecular sieve obtained in step (1) is added and stirred continuously, and ammonia water is added dropwise to adjust the pH value to 5 to form a sol. The sol is sprayed onto the surface of the cordierite carrier by a rotary spraying technique, and the spraying is repeated several times, and the sol is aged to make the coating amount reach 200 g / L, and then dried at 60°C for 10 hours and calcined at 500°C for 4 hours to obtain a supported cordierite catalyst.
[0040] Comparative Example 1
[0041] A Rh-modified alumina-Pt three-way catalyst, the preparation method of which comprises the following steps:
[0042] Step (1) 200 g of porous alumina is dispersed in water, rhodium nitrate solution (containing 3.57 g of rhodium nitrate) is added dropwise, and after stirring evenly, ammonium carbonate solution is added dropwise, and the pH value is controlled to be 5. The alumina is filtered out, vacuum dried at 50° C. for 10 h, and calcined at 400° C. for 2 h to obtain Rh-modified alumina.
[0043] Step (2) 3 mL of hydrazine hydrate, 3 g of polydextrose, and 40 mL of ethanol were dissolved in 100 g of water, and a platinum nitrate solution (containing 0.208 g of platinum nitrate) was added dropwise, and the mixture was placed in a water bath at 60° C. for 6 h, and then washed with ethanol several times and dispersed in ethanol to obtain a Pt colloid.
[0044] Step (3): Dissolve yttrium nitrate (20 g in terms of yttrium oxide), lanthanum nitrate (20 g in terms of lanthanum oxide), cerium nitrate (160 g in terms of cerium oxide), and zirconium nitrate (600 g in terms of zirconium oxide) in water, add the Pt colloid obtained in step (2), and place in a water bath at 80°C for 3 h. Then, add the Rh-modified alumina obtained in step (1) and continue stirring. Add ammonia water to adjust the pH value to 5 to form a sol. Spray the sol onto the surface of the cordierite carrier by rotary spraying technology, spray repeatedly for several times, age until the coating amount reaches 200 g / L, dry at 60°C for 10 h, and calcine at 500°C for 4 h to obtain a supported cordierite catalyst.
[0045] Comparative Example 2
[0046] A three-way catalyst supported on a Ag-modified molecular sieve, the preparation method of which comprises the following steps:
[0047] Step (1) 300 g of CHA type SSZ-13 molecular sieve was dispersed in water, and a silver nitrate solution (containing 6 g of silver nitrate) was added dropwise, and after stirring evenly, an ammonium carbonate solution was added dropwise to control the pH to 5. The molecular sieve was filtered out, vacuum dried at 50° C. for 10 h, and calcined at 400° C. for 2 h to obtain an Ag-modified molecular sieve.
[0048] Step (2): dissolve praseodymium nitrate (21 g in terms of praseodymium oxide), lanthanum nitrate (21 g in terms of lanthanum oxide), cerium nitrate (280 g in terms of cerium oxide), and zirconium nitrate (378 g in terms of zirconium oxide) in water, add platinum nitrate solution (containing 6.23 g of platinum nitrate), and place in a water bath at 80° C. for 3 h, then add the Ag-modified molecular sieve obtained in step (1), continue stirring, and drop ammonia water to adjust the pH value to 5 to form a sol. Spray the sol onto the surface of a cordierite carrier by a rotary spraying technique, spray repeatedly for several times, age until the coating amount reaches 200 g / L, dry at 60° C. for 10 h, and calcine at 500° C. for 4 h to obtain a supported cordierite catalyst.
[0049] Results: The catalyst samples obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were aged under the same conditions in a high-temperature tube furnace at 1050°C for 20 hours, and then packaged into a purifier. The whole vehicle emission test was carried out according to the Worldwide Light Vehicle Harmonized Test Cycle (WLTC) Type I test. The engine displacement of the test vehicle was 1.6L. The emission test results are shown in Table 1 below.
[0050] Table 1: Comparison of catalytic performance of the catalysts obtained in Examples 1 to 3 and Comparative Examples 1 to 2:
[0051] THC(mg / km) CO(mg / km) <![CDATA[NO X (mg / km)]]> Example 1 46.1 346.6 32.1 Example 2 37.3 310.3 29.2 Example 3 42.6 335.9 27.6 Comparative Example 1 62.4 397.2 45.3 Comparative Example 2 66.9 536.8 58.9
[0052] Note: THC (Total Hydrocarbons) in Table 1 is the abbreviation for the total amount of hydrocarbons contained in the gas.
[0053] As shown in Table 1 above, the results of the catalyst performance evaluation show that the three-way catalysts prepared in Examples 1 to 3 of the present invention have a high THC, CO, and NO x Compared with the control group, the indicators were improved by about 35.0%, 29.1% and 43.1% respectively on average, showing a good removal effect and excellent exhaust gas purification ability.
[0054] The present invention loads a Pt-coated cerium-zirconium solid solution on an Ag-modified molecular sieve. The cerium-zirconium solid solution coating of Pt can effectively avoid the sintering and agglomeration of the noble metal Pt at high temperature. The high specific surface area of the molecular sieve promotes the high dispersion of Ag and exposes more active centers, thereby reducing the amount of noble metals and saving production costs, while further improving the catalytic performance of the three-way catalyst. The catalyst prepared by coating on a ceramic carrier has the remarkable characteristics of high performance and low cost.
[0055] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the embodiments, ordinary technicians in the field should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of protection requested by the claims of the present invention.
Claims
1. An Ag-Pt high-performance and low-cost three-way catalyst, characterized in that: The catalyst is prepared by coating Pt colloid with cerium-zirconium solid solution, loading it on Ag-modified molecular sieve, and then spraying it on a carrier.
2. The Ag-Pt high-performance and low-cost three-way catalyst according to claim 1, characterized in that: The molecular sieve is selected from one or more of MFI type ZSM-5, CHA type SSZ-13, Beta type, and HY type molecular sieves.
3. The Ag-Pt high-performance and low-cost three-way catalyst according to claim 1, characterized in that: The weight ratio of the molecular sieve to silver nitrate is 20-180:
1.
4. The Ag-Pt high-performance and low-cost three-way catalyst according to claim 1, characterized in that: The mass ratio of Ag to Pt is 10:1~1:
10.
5. The Ag-Pt high-performance and low-cost three-way catalyst according to claim 1, characterized in that: The molecular sieve accounts for 10-40% by weight in the entire coating.
6. The Ag-Pt high-performance and low-cost three-way catalyst according to claim 1, characterized in that: The mass ratio of CeO2 in the cerium-zirconium solid solution is 5% to 60%.
7. The Ag-Pt high-performance and low-cost three-way catalyst according to claim 1, characterized in that: The mass ratio of yttrium oxide, lanthanum oxide and praseodymium oxide in the cerium-zirconium solid solution is 1% to 10%.
8. The Ag-Pt high-performance and low-cost three-way catalyst according to claim 1, characterized in that: The carrier is a ceramic or cordierite carrier.
9. A method for preparing a Ag-Pt high-performance and low-cost three-way catalyst, characterized in that The following steps are involved: Step (1) dispersing the molecular sieve in water, dropping a silver nitrate solution, stirring evenly, dropping an ammonium carbonate solution, controlling the pH value to be 4-6, filtering out the molecular sieve, vacuum drying at 40-60° C. for 8-12 h, and calcining at 300-500° C. for 1-3 h to obtain an Ag-modified molecular sieve; Step (2) dissolving hydrazine hydrate, polydextrose and ethanol in water, dropping platinum nitrate into it, bathing it in water at 50-80°C for 4-8 hours, then washing it with ethanol several times and dispersing it in ethanol to obtain Pt colloid; Step (3) dissolving one or more selected from yttrium nitrate, lanthanum nitrate, praseodymium nitrate, cerium nitrate and zirconium nitrate in water, adding the Pt colloid obtained in step (2), and then heating in a water bath at 50-90°C for 2-4 hours, then adding the Ag-modified molecular sieve obtained in step (1) and continuing to stir, and adding ammonia water to adjust the pH value to 4-6 to form a sol; spraying the sol on the surface of the cordierite carrier by a rotary spraying technique, repeatedly spraying for several times, aging, drying at 40-80°C for 8-12 hours, and calcining at 400-600°C for 2-4 hours to obtain a supported cordierite catalyst.
10. The method for preparing the Ag-Pt high-performance and low-cost three-way catalyst according to claim 9, characterized in that: The ratio of hydrazine hydrate, polydextrose, ethanol and platinum nitrate is 4-10 mL: 2-5 g: 20-60 mL: 0.1-1 g.